Komposit Zeolit-Polivinil Alkohol sebagai Adsorben untuk Menurunkan Kesadahan Air Tanah - Anang Takwanto; Yanty Maryanty; Anugrah Windy Mustikarini; Dina Wulan Sari; Rizki Kurnia Juliansyah (Universitas Andalas, 2023)
Granular zeolite-polyvinyl alcohol (PVA) composites without glutralaldehyde and zeolite-PVA composites with the addition of glutaraldehyde were carried out in this study and used as adsorbents. This study aims to reduce groundwater hardness, determine the optimum zeolite size in composite mixtures, and determine the characterization of functional groups in composites. The stages of the research included: preparation and activation of zeolite with variations in zeolite sizes of 100, 60 and 45 mesh and variations in composition of zeolite-polyvinyl alcohol 1:1; 1:2; 2:1; 2:3 and 3:2. Furthermore, the preparation of PVA solution concentration of 9% and the formation of the composite. The results showed that the optimum size of the zeolite on the composite without glutaraldehyde was 60 mesh with a decrease in hardness of 68% while the ratio of the optimum zeolite-PVA composition was at a ratio of 3:2 with a decrease in hardness of 34 mg/L. The results of Langmuir and Freundlich isotherm analysis showed the presence of chemical bonds because the determination value (R2) of the adsorption isotherm was > 0.9. The results of functional group characterization showed OH- in the zeolite-PVA composite without glutaraldehyde at a wavelength of 3363.01 cm-1 while in the composite with glutaraldehyde at a wavelength of 3345.89 cm-1. The C=C functional group appeared at a wavelength of 1628.73 cm-1 for the zeolite-PVA composite without glutaraldehyde and 1635.86 cm-1 for the composite with glutaraldehyde. At a wavelength of 788.70 cm-1 and 794.40 cm-1, the Si-O symmetric stretching vibrations show in the zeolite structure.